Natural history of functional gastrointestinal disorders: a 12-year longitudinal population-based study - Halder, Smita L S; Locke, 3rd, G Richard; Schleck, Cathy D; Zinsmeister, Alan R; Melton, 3rd, L Joseph; Talley, Nicholas J (Gastroenterology (New York, N.Y. 1943), 2007)
Functional gastrointestinal disorders (FGID) are common in the community. The natural history of FGID is unknown because of a lack of prospective population-based studies and the indistinct nature of the phenotype. We sought to report the natural history of FGID in a US population. This prospective cohort study used data from multiple validated surveys of random samples of Olmsted County, MN, residents over a mean of a 12-year period between 1988 and 2003 (n = 1365). The surveys measured gastrointestinal symptoms experienced during the past year. Each subject received a minimum of 2 surveys. Point prevalence, onset, and disappearance rates and transition probabilities were calculated for individual FGIDs. Between the initial and final surveys, the point prevalences (per 100 residents) were stable for irritable bowel syndrome (8.3% and 11.4%, respectively) and functional dyspepsia (1.9% and 3.3%, respectively). The onset of each of the disorders studied was greater than the disappearance rate, but the transition probabilities varied across the different subgroups. Among people with symptoms at baseline, approximately 20% had the same symptoms, 40% had no symptoms, and 40% had different symptoms at follow-up. Although the prevalence of the FGID was stable over time, the turnover in symptom status was high. Many episodes of symptom disappearance were due to subjects changing symptoms rather than total symptom resolution. This transition between different FGIDs suggests a common etiopathogenesis.